New Cryptanthus species (Bromeliaceae: Bromelioideae) from the State of Bahia, Brazil - de Souza, Everton Hilo; Leme, Elton M.c. (Phytotaxa, 2021)
The authors describe and illustrate four new species of Cryptanthus: C. flesherii, C. lutandensis, C. santosii, and C. solidadeanus. The affinities and distinctness of the new species are supported by the combination of geographical distribution, ecological preference, and morphological characters regarded as the most useful to distinguish taxa in “Cryptanthoid complex”. All described species were recovered as critically endangered. A distribution map as well as taxonomic comments are presented.